2021
DOI: 10.1172/jci.insight.140180
|View full text |Cite
|
Sign up to set email alerts
|

Differential role of MLKL in alcohol-associated and non–alcohol-associated fatty liver diseases in mice and humans

Abstract: Hepatocellular death contributes to progression of alcohol–associated (ALD-associated) and non–alcohol-associated (NAFL/NASH) liver diseases. However, receptor-interaction protein kinase 3 (RIP3), an intermediate in necroptotic cell death, contributes to injury in murine models of ALD but not NAFL/NASH. We show here that a differential role for mixed-lineage kinase domain–like protein (MLKL), the downstream effector of RIP3, in murine models of ALD versus NAFL/NASH and that RIP1-RIP3-MLKL can be used as biomar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…These findings offer a tantalising clue that necroptosis may contribute to this disease, depending on the trigger. In contrast to NAFLD, MLKL does not appear to play a statistically significant role in acute or chronic alcoholic liver disease [58].…”
Section: Metabolic Diseasementioning
confidence: 76%
“…These findings offer a tantalising clue that necroptosis may contribute to this disease, depending on the trigger. In contrast to NAFLD, MLKL does not appear to play a statistically significant role in acute or chronic alcoholic liver disease [58].…”
Section: Metabolic Diseasementioning
confidence: 76%
“…The difference could be caused by different steatotic models utilized in the studies, as well as the lipid composition and the extent of inflammation in NAFLD vs ALD as discussed above. Notably, a recent study by Miyata et al found that MLKL played a differential role in ALD and NAFLD [14]. Although MLKL protein level and plasma membrane translocation were both significantly increased in HFF-fed mouse livers, there was no change in MLKL protein level or plasma membrane translocation in chronic plus binge ethanol mouse livers.…”
Section: Discussionmentioning
confidence: 91%
“…However, how fatty liver increases IR injury remains unclear, which has halted the use of fatty livers in liver transplantation. Accumulating evidence suggests that necroptosis is critical in the pathogenesis of inflammatory liver diseases including NAFLD, ALD, and hepatic IR injury [10][11][12][13][14][15]. Necroptosis is a form of regulated cell death, which is mediated by three key molecules: receptor-interacting protein kinase 1 (RIP1), receptor-interacting protein kinase 3 (RIP3), and mixed lineage kinase domain-like protein (MLKL) [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…RIPK3, the key molecule of necroptosis signalling, was induced in murine models after ethanol exposure 3,50–52 . The biopsy samples from ALD and alcoholic liver cirrhosis patients showed increased RIPK3 and p‐MLKL expression, but not RIPK1, implying the important role of necroptosis in the occurrence and development of ALD 3,51,53–55 …”
Section: Roles Of Necroptosis In Alcoholic Liver Diseasementioning
confidence: 99%
“…Compared with WT mice, the expression of inflammatory cytokines after Gao‐binge ethanol feeding was decreased in MLKL −/− mice, whereas the expression of chemokines was independent of MLKL genotype, as detected by chemokine (C‐X‐C motif) ligand 1 (Cxcl1) and Cxcl2 expression. Similarly, Gao‐binge ethanol–induced neutrophil accumulation was not ameliorated by MLKL knockout 54 . In addition, Gao‐binge feeding–stimulated cytochrome P450 2E1 (CYP2E1) induction and endoplasmic reticulum (ER) stress were not affected by MLKL deletion, indicating that MLKL is not critical for ethanol‐induced liver injury.…”
Section: Roles Of Necroptosis In Alcoholic Liver Diseasementioning
confidence: 99%